Analisis Tingkat Kesehatan Bank Syariah Dengan Menggunakan Metode CAMEL (Study Pada Bank Muamalat Indonesia Periode 2008-2012) - Kusumawati, Finda Trianggita; ati, Sumi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
Role in establishing a national banking is one sector of the economy that are expected to play an active role in supporting the development of national and regional activities. In the banking world, the trust factor is a very important thing. Bank rating will also affect the assessment of potential investors to a bank. Therefore this study aimed to analyze the soundness of the Bank Muamalat Indonesia occurred in the period 2008-2012 by using CAMEL. This type of research is a descriptive study to analyze the data. The data used in this study is in the form of bank financial statements. The research object is Bank Muamalat Bank Muamalat Indonesia because it is a founding pioneer of Islamic banking in Indonesia so it can be measured by the development of Islamic banking. CAMEL variables are used to analyze the soundness of Bank Muamalat Indonesia consists of 6 (six) ratio: capital adequacy ratio (CAR), asset quality (KAP), Productive Asset Allowance (PPAP), net profit margin (NPM), Return on assets (ROA), operating expenses on operating income (ROA), and the loan to deposit ratio (LDR). Based on the analysis of the soundness of Islamic banks using the 6 (six) CAMEL ratio, the final result shows that Bank Muamalat Indonesia shows that over the period 2008-2012, the bank is healthy. CAMEL score in 2008 was 92.05 (HEALTH), the year 2009 was 91.5 (HEALTH), the year 2010 was 94.6 (HEALTH), in 2011 was 95 (HEALTH), in 2012 was 95 (HEALTH). Â Kata Kunci : Kesehatan Bank, Bank Syariah, CAMEL